Development of Digital-Based Ludo Game Media Material on How We Live and Grow in the Science Subject for Grade V in Elementary Schools - Putrawan, Putu Rendy; Primayana, Kadek Hengki; Pancaria, I Nyoman (Jurnal Teknologi Pendidikan, 2025)
This study aims to develop digital-based Ludo game media as a learning media on the material "How We Live and Grow" in the subject of Natural and Social Sciences (IPAS) for grade V Elementary School students. Media development uses the ADDIE model which includes the stages of analysis, design and development. This digital-based Ludo game media is designed to increase student involvement and understanding through active and enjoyable learning. The validity results from media experts, material experts and language experts show that this media is declared valid and feasible to use. Practicality tests on students show that this media is practical and effective in increasing interest in learning and understanding of the concept of IPAS material. Thus, digital-based Ludo game media can be an alternative innovative learning media and support the active learning process in grade V Elementary School.